Soil-walter properties of a Latosol Vermelho Escuro of the Federal District - Wolf, James M.; Soares, Wilson V. (Pesquisa Agropecuaria Brasileira, 2014)
Data are presented which characterize the water holding properties of a Latosol Vermelho Escuro of the Federal District. These data were obtained by relating in situ measurements of soil-water tension with gravimetric determinations of soil-water content. Use of this information has been applied to determine water availability for cropping on this soil. The soil studied may be characterized by rapid infiltration and extensive internal drainage. Like a sand, this clayey Oxisol releases two-thirds of the stored water between 1/10 and 1 bar. Water availability is limited to approximately 30-40 mm per 30 cm of soil. The unfavorable soil-water relations of this soil, together with less than ideal rainfall conditions and rooting regimes which may be limited by aluminum toxicity makes water relations critical and cropping risky. Since management of this soil for cropping will require costly inputs, it may be difficult to repay investments when yields vary greatly in the absence of controlled water management.